1997
DOI: 10.1038/nbt1297-1378
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine secretion of human insulin and growth hormone by exocrine glands of the gastrointestinal tract

Abstract: The exocrine pancreas, liver, and submandibular glands of the rat were used to express and secrete two exogenous, human protein hormones (growth hormone and insulin) into blood at physiological concentrations. Transfection, expression, and secretion were achieved by the in vivo retrograde injection of plasmid DNA into the secretory ducts of these glands. Pancreatic acinar cells secreted physiological concentrations of growth hormone into the circulation, and its secretion was enhanced by cholinergic stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 17 publications
2
65
0
1
Order By: Relevance
“…5, which is published as supporting information on the PNAS web site). Although it would seem surprising that a presumptive endocrine factor is strongly expressed in an exocrine gland, there have been numerous reports of other growth factors being expressed in salivary glands (15)(16)(17)(18)(19), and it has been shown that endocrine factors expressed after introduction of DNA into these glands are readily secreted into the bloodstream (20,21). Indeed, a body of opinion contends that salivary glands have a mixed exocrine and endocrine function (22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…5, which is published as supporting information on the PNAS web site). Although it would seem surprising that a presumptive endocrine factor is strongly expressed in an exocrine gland, there have been numerous reports of other growth factors being expressed in salivary glands (15)(16)(17)(18)(19), and it has been shown that endocrine factors expressed after introduction of DNA into these glands are readily secreted into the bloodstream (20,21). Indeed, a body of opinion contends that salivary glands have a mixed exocrine and endocrine function (22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…There are also strong HLA associations. 29 and exocrine pancreas. 29 The most productive results have been achieved by using vector carrying furin-modified insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Acinar cells are capable of exporting protein into the bloodstream, as well as the ductal lumen, and blood borne proteins enter the portal circulation. 29,31,32 High level gene transfer in the rat and mouse pancreas have been shown using adenoviral vectors. Intra-ductal and direct intra-pancreatic injections are efficient ways to deliver adenoviral vector into the mouse pancreas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preproinsulin biosynthesis has been achieved in a variety of endocrine cells like K-cells (48) or cells from pituary (49)(50)(51), exocrine pancreas (52), and submandibular glands (42), as well as in nonendocrine cells like muscle cells (53,54), and fibroblasts (55). However, in some of the endocrine cell lines (e.g.…”
Section: Engineering Of a Surrogate β-Cellmentioning
confidence: 99%